Retorik dan pemaparan imej lelaki dalam bahasa iklan majalah men's health / Khoo Chu Pheng - Khoo, Chu Pheng (2012)
This study aims to review the male advertisement from Men's Health magazine, with focus on the elements rhetoric and language features used in advertisement to prominence the male image, and investigation male image through advertising language. Male’s image includes stereotypes and masculinity, as well as metrosexual image. Study data collected from Men's Health magazine, and the title or slogan in the advertisement examined. Data analyzed by the method of Content Analysis. In data analysis and discussion qualitative and quantitative methods are used. This study found that elements rhetoric that most frequently used are hyperbole followed by rhetoric questions and paronomasia. Hyperbole used as excessive words to expand the product’s function. Rhetorical question was intended to arouse curiosity reader. For paronomasia, it used to convey compact messages with short sentence. Most rarely rhetorics used are rhyme and catchword repetition, due to the less slight effect on reader compared to the other elements rhetoric. In terms of male’s image, the most stereotype and masculinity used in advertisement language is ‘bread winner’ followed by ‘fighter’ and the least is ‘give 'em hell’. It shows that people are now concerned with the character that willing to work hard and fight for victory whereas aggressive acts are not pleasant by the public. The metrosexual image that concerned to the appearance and fashion are also displayed in the advertisements. In conclusion, elements rhetorical are used to convey the message effectively, included support of male image that used to promote products which advertised. In this aspect, male image displayed in the advertisement is through the appearance of male models and language features. However, male image is changing where aggressiveness is no longer adored, and while image metroseksual began to be accepted in the society. This study’s findings may contribute to the field of local advertising, as well as the field of language and linguistic.